Economic crisis and participation in Adult Education: A qualitative investigation with primary teachers in Greece - Papalexopoulou, Maria; Rorou, Vassiliki; Karalis, Thanassis (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
In this research, a quantitative approach (semi-structured interviews) is used to investigate the views of primary education teachers, concerning their participation in continuing education programs. The investigation of the motives and barriers to their participation is based on the Morstain & Smart and Cross typologies, while the present researchs findings are compared to those of a quantitative research in Greece. As it turns out from the findings of the research, the recent severe economic crisis largely restrains the primary education teachers options for participation in continuing education and lifelong learning.